Lutzomyia whitmani is the main vector of American Cutaneous Leishmaniasis in the Brazilian Federal District and the most prevalent species in residential areas of the Administrative Region of Sobradinho - Mariana Boff Barreto; Andrea Lisboa Carneiro; Fernando Araripe Gonçalves Torres; Raimunda Nonata Ribeiro Sampaio (Sociedade Brasileira de Dermatologia, 2014)
Although cases of cutaneous Leishmaniasis have been reported in Brasilia - DF, its mode of transmission is still unknown. Center of Disease Control traps (CDC trap) placed around Sobradinho, a periurban area in the Brazilian Federal District, were able to capture a sample of phlebotomines composed of 89% Lutzomyia whitmani, 7% Lu. bacula, and 3% Lu. davisi specimens. Being of 77% of these specimens were captured in peridomiciliary. PCR analyses showed that the specimens were negative for Leishmania DNA. However, the high prevalence of Lu. Whitmani in the studied region suggests that it may be the main vector for the transmission of Leishmaniasis in peridomiciliary areas in the studied region.